Renewal coaching fieldbook : how effective leaders sustain meaningful change - Allison, Elle, 1960-; Reeves, Douglas B., 1953- (San Francisco : Jossey-Bass, 2011)
'The field of business coaching is a recognized, rapidly growing discipline, used by many individuals and organizations to improve the workplace performance. Part of a series of books, Renewal Coaching Fieldbook provides proven, research-based, sustainable strategies. Including website access to resources, assessments, downloads, research, and case studies, this book offers a wiki environment for readers to contribute and share their own experiences. Additionally, the Fieldbook contains cases, tips, and resources for a deeper understanding for executive coaches, teachers, volunteers or anyone who fits into the role of a'coach.''--
Includes bibliographical references and index.
Keywords: Leadership; Organizational change; Employees -- Coaching of; Personal coaching; Change (Psychology)